Study of History and Type of Firewall - Shalini (Innovative Research Thoughts, 2017)
A firewall may block any harmful data from entering your network. Using a predetermined set of rules, firewalls prevent malicious traffic from entering a network. Users inside the network might be blocked from accessing specific resources by implementing these policies. The basic premise behind firewalls is that data travelling across networks from less secure locations should be verified and reviewed before being allowed access to more secure locations. In this way, access to a restricted area of a network can be denied to unwanted individuals, machines, and programmes. Without firewalls, hackers may easily get access to your network and use its computers and devices to launch attacks.